Breastfeeding Pattern and Gain in Weight Among a Group of Urban Infants - Ahmed, Luthfor; Edib, Khaleda; Huda, Syed Nazmul; Islam, SK Nazrul; Khan, Md Nazrul Islam (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.29-36